2013
DOI: 10.2119/molmed.2013.00136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Erythropoietin in Murine-Induced Pluripotent Cell-Derived Panneural Progenitor Cells

Abstract: Induced cell fate changes by reprogramming of somatic cells offers an efficient strategy to generate autologous pluripotent stem (iPS) cells from any adult cell type. The potential of iPS cells to differentiate into various cell types is well established, however the efficiency to produce functional neurons from iPS cells remains modest. Here, we generated panneural progenitor cells (pNPCs) from mouse iPS cells and investigated the effect of the neurotrophic growth factor erythropoietin (EPO) on their survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In another study, the systemic administration of EPO for 3 weeks was found to increase the number of CA1/CA3 neurons by enhancing adult neurogenesis without entering the cell cycle (Hassouna et al, 2016). Furthermore, EPO facilitates neurodifferentiation while reducing cell proliferation and neurosphere formation induced by mouse induced pluripotent stem (iPS) cell-induced panneural progenitor cells (Offen et al, 2013). Therefore, EPO treatment can increase the generation of newborn neuronal cells partly by elevating differentiation into neurons.…”
Section: Neural Progenitor Cell Proliferationmentioning
confidence: 98%
“…In another study, the systemic administration of EPO for 3 weeks was found to increase the number of CA1/CA3 neurons by enhancing adult neurogenesis without entering the cell cycle (Hassouna et al, 2016). Furthermore, EPO facilitates neurodifferentiation while reducing cell proliferation and neurosphere formation induced by mouse induced pluripotent stem (iPS) cell-induced panneural progenitor cells (Offen et al, 2013). Therefore, EPO treatment can increase the generation of newborn neuronal cells partly by elevating differentiation into neurons.…”
Section: Neural Progenitor Cell Proliferationmentioning
confidence: 98%